Potential for direct and indirect plant growth promotion and heterologous expression of biocontrol enzymes from slow-growing bacteria - Jesuino, Blenda de Freitas Rodrigues (Universidade Federal de Viçosa, 2025)
Economic factors, physical space limitations, and agricultural production losses due to phytopathogens pose significant challenges for sustainable agriculture. The main current responses to these challenges are the use of chemical fertilizers and pesticides. In addition to or instead of these challenges, more sustainable solutions have been developed, above all through the use of biofertilizers and biopesticides. With the growing demand for plant growth-promoting bacterias (PGPBs) and biocontrol bacterias, new microbial groups have been prospected. The promising indications of slow-growing bacteria for these purposes led to their further exploration in this work. However, given that their long life cycle can make scaling up difficult, the approach of heterologous expression of biocontrol enzymes encoded by slow- growing bacteria was also used. The diversity of the slow-growing isolates was evidenced through phylogenetic analysis, which revealed that the 11 sequenced isolates are distributed in seven distinct genera. A wide variety of genes related to plant growth-promoting traits (PGPT) were detected in all the isolates, with the most abundant genetic traits being related to heavy metal detoxification, osmotic stress neutralization, vitamin production, chemotactic motility, secretion systems, and siderophore production. The in vitro detection of PGPT, carried out to validate the genes predicted in silico, confirmed the ability of slow-growing bacteria to promote plant growth. The genes encoding biocontrol enzymes were also prospected in silico and validated in vitro. Biosynthetic gene clusters (BGC) prospecting detected 13 distinct BGC classes and a frequency of 57 clusters, as well as seven classified as "other". In the paired culture trials between the slow-growing bacterial isolates and phytopathogenic fungi, many bacterial isolates showed antagonism to Fusarium equiseti CCF422, Fusarium oxysporum CCF184, Rhizoctonia solani 2930, and Sclerotinia sclerotiorum 15B, with average inhibition above 20%. A total of 168 defense genes related to 30 defense systems were detected throughout the genomes of the 11 slow-growing isolates. In addition, a total of 39 resistance genes were also detected, distributed across the genomes of seven isolates and three isolates with virulence genes. In addition to the prolonged growth time, the presence of virulence genes also means that the biocontrol potential of the isolates has to be assessed indirectly, which can be done through the heterologous expression of proteins. Heterologous expression of the enzymes chitinase, exo-beta- 1,3-glucanase, and N-acetylmuramyl-L-alanine amidase was carried out. The recombinant enzymes proved to be active in the transformed Escherichia coli BL21, both in the degradation of the substrate and in the culture paired with phytopathogenic fungi. However, protein extraction revealed that the recombinant enzymes remained in the insoluble fraction, from which they were purified and then refolded. However, only glucanase showed enzymatic activity, making it necessary to modify the refolding buffer to recover the three-dimensional structure of chitinase and amidase. These preliminary results provide good prospects for the future application of a biopesticide composed of recombinant biocontrol enzymes. Keywords: plant growth-promoting bacterias (PGPBs); enzyme phytopathogenic fungus; dual culture; Recombinant protein prospecting;

Os fatores econômicos, limitações de espaço físico e perdas da produção agrícola causadas por fitopatógenos representam grandes desafios para uma agricultura sustentável. As principais respostas atuais para esses desafios são o uso de fertilizantes e pesticidas químicos. Em adição ou substituição, esses desafios têm sido enfrentados com soluções mais sustentáveis, sobretudo com o uso de biofertilizantes e biopesticidas. Com a crescente demanda por bactérias promotoras do crescimento vegetal (PGPBs) e de biocontrole, novos grupos microbianos têm sido prospectados. Os indicativos promissores das bactérias de crescimento lento para esses fins basearam sua maior exploração no presente trabalho. Porém, pensando que o ciclo de vida prolongado pode dificultar o escalonamento, também foi utilizada a abordagem da expressão heteróloga de enzimas de biocontrole codificadas por bactérias de crescimento lento. A diversidade dos isolados de crescimento lento foi evidenciada através das análises filogenéticas, que revelaram que os 11 isolados estão distribuídos em sete gêneros distintos. Foi detectada uma grande variedade de genes relacionados aos traços de promoção do crescimento vegetal (PGPT) em todos os isolados, sendo os traços genéticos mais abundantes relacionados à detoxificação de metais pesados, neutralização de estresse osmótico, produção de vitaminas, motilidade quimiostática, sistemas de secreção e produção de sideróforos. A detecção in vitro dos PGPTs realizada para validação dos genes previstos in silico confirmou a capacidade das bactérias de crescimento lento em promover o crescimento vegetal. Os genes codificantes de enzimas de biocontrole também foram prospectados in silico e validados in vitro. A prospecção por clusters de genes biossintéticos (BGC) detectou 13 classes de BGCs distintas e frequência de 57 clusters, além de sete classificados como “outros”. Nos ensaios de cultura pareada entre as bactérias de crescimento lento e os fungos fitopatogênicos, muitos isolados bacterianos se mostraram antagonismo ao Fusarium equiseti CCF422, Fusarium oxysporum CCF184, Rhizoctonia solani 2930, and Sclerotinia sclerotiorum 15B, com inibição média acima de 20%. Foram detectados um total de 168 genes de defesa relacionados a 30 sistemas de defesa em todo o genoma dos 11 isolados de crescimento lento. Além disso, também foram detectados um total de 39 genes de resistência distribuídos no genoma de sete isolados e três isolados com genes de virulência. Além do tempo de crescimento prolongado, a presença de genes de virulência também faz com que o potencial de biocontrole dos isolados tenha que ser acessado de forma indireta, o que pode ser feito através da expressão heteróloga de proteínas. Foi realizada a expressão heteróloga das enzimas quitinase, exo-beta-1,3-glucanase e N- acetylmuramyl-L-alanine amidase. As enzimas recombinantes se mostraram ativas na Escherichia coli BL21 transformada tanto na degradação do substrato quanto na cultura pareada com fungos fitopatogênicos. Porém, a extração proteica revelou que as enzimas recombinantes ficaram na fração insolúvel, de onde foram purificadas e em seguida redobradas. Entretanto, apenas a glucanase apresentou atividade enzimática, sendo necessário modificar o tampão de redobramento para recuperar a estrutura tridimensional da quitinase e amidase. Estes resultados preliminares dão boas perspectivas para a futura aplicação de um biopesticida composto por enzimas recombinantes de biocontrole. Palavras-chave: bactérias promotoras do crescimento vegetal (PGPBs); prospecção enzimática; fungo fitopatogênico; Cultura dupla; proteína recombinante
Potencial de promoção do crescimento vegetal direto e indireto e expressão heteróloga de enzimas de biocontrole de bactérias de crescimento lento
Keywords: Rizobactérias promotoras de crescimento de plantas; Enzimas; Fungos fitopatogêncios; Proteínas recombinantes; Microbiologia Agrícola